2014
DOI: 10.1016/j.bjorl.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sugarcane biopolymer gel injected in rabbit vocal fold

Abstract: We show that in spite of producing an inflammatory reaction in vocal fold tissues, the material remained in vocal fold throughout the study period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
(22 reference statements)
0
2
0
3
Order By: Relevance
“…The effect of biopolymer gel derived from sugarcane on healing of traumatic oral ulcers: an experimental study membranes, sponges, granules, and prostheses, has been extensively studied for application in the medical industry 10 . During the experiments, no clinical signs of infection, allergies, intoxication, or tissue extrusion were observed 7,11,12 .…”
Section: Introductionmentioning
confidence: 93%
“…The effect of biopolymer gel derived from sugarcane on healing of traumatic oral ulcers: an experimental study membranes, sponges, granules, and prostheses, has been extensively studied for application in the medical industry 10 . During the experiments, no clinical signs of infection, allergies, intoxication, or tissue extrusion were observed 7,11,12 .…”
Section: Introductionmentioning
confidence: 93%
“…In both cases the SCB was replaced by collagen fibers, which retained at least partially the mass effect of the substance on the applied site 17,18 . In a recent work, Leão et al 19 studied the inflammatory reaction caused by the injection of the vocal fold SCB in rabbits. The authors observed that the polymer had rheological characteristics compatible with use in long-term treatment of glottal insufficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Soma-se a isso o fato desse animal ser dócil e de fácil manuseio. Além disso, a literatura mostra outros trabalhos que utilizaram coelhos como modelo animal para estudo de enxertos para pregas vocais (4,36,41,42) . O simples espessamento desse epitélio ou, nos casos mais graves, a ulceração ou formação de granulomas, pode ter um impacto negativo muito importante na qualidade vocal após uma IL.…”
Section: Delineamento Do Estudo E Metodologiaunclassified
“…O simples espessamento desse epitélio ou, nos casos mais graves, a ulceração ou formação de granulomas, pode ter um impacto negativo muito importante na qualidade vocal após uma IL. Em outros estudos (4,26,36,41,42) foi utilizada a reação inflamatória ao material aplicado cirurgicamente dentro da prega vocal, como fator preditivo para os resultados funcionais do material em questão. A presença de uma reação inflamatória excessiva ao material escolhido para a IL era ligada a complicações, insucessos nesse procedimento e má qualidade vocal com vários materiais, incluindo a HCa (3,24) .…”
Section: Delineamento Do Estudo E Metodologiaunclassified
See 1 more Smart Citation